The Role Of Computed Tomography In The Diagnosis Of Acute Abdominal Diseases - pcadmin, Khodjimuratov Davronjon Ikramalievich (Peerian Journals Publishing, 2025)
Computed tomography (CT) is a diagnostic method that occupies an important place in modern medicine, which makes it possible to accurately and in detail describe the internal structure of the human body. This method is especially effective in diagnosing acute abdominal diseases. Acute abdominal diseases, such as appendicitis, pancreatitis, intestinal obstruction, and internal bleeding, are emergency conditions that need to be quickly identified and treated properly. Computed tomography plays an important role in the detection of these diseases, as it provides high-resolution images and shows in detail the state of internal organs.
Keywords: Acute abdominal diseases; computed tomography